Conjunctive planning of surface and groundwater resources in canal command area of Odisha- a success story - Rani Sethi, R.; B. Singandhupe, R.; Kumar, A. (Health, Safety and Environment, 2020)
Conjunctive planning of irrigation through bore wells, dug wells and water harvesting structures along with farmers’ participatory approach in Pattamundai canal command area of Odisha could increase cropping intensity from 151% to 300% with high value and less water requirement crops. Interventions showed that during long dry spell period in kharif season and non availability of canal water, use of groundwater up to 20 % of the crop water demand could enhance crop yield up to 21 %. Utilizing water from dug well, for three crops (short duration paddy- potato/ radish- bitter gourd) in a year recorded highest net return of Rs 87368/ha against two crops (paddy - brinjal) without depletion of groundwater level. Further, highest water productivity (kg fruit yield/m3of water used) was observed in potato (6.67-8.41) followed by brinjal (4.06-4.42).